Pedagogical Approaches in Catholic Choir Training: a Case Study of Santa Maria Fajar Church, Central Lampung - Saputra, Vincensius Galih; Afrizal Yuda Setiawan; Prisma Tejapermana; Bian Pamungkas (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Objective: This study aims to describe the learning process of the Catholic choir at Santa Maria Fajar Church, Mataram, Central Lampung, specifically regarding the learning mechanisms and methods applied. Method: The study employed a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The theoretical basis used was behaviorist theory, which emphasizes the relationship between stimulus and response through repeated practice. Results and Discussion: The results of the study indicate that the choir learning process proceeded systematically through three stages: initial activities in the form of vocalization, core activities in the form of liturgical song practice, and closing activities in the form of evaluation. The learning methods applied included drills, demonstrations, and peer tutoring to address various technical challenges, such as notation reading, intonation, and harmonization. Evaluation was conducted to monitor the development of articulation, dynamics, and appreciation of the songs. Conclusion: This study concludes that the Catholic choir learning process at Santa Maria Fajar Church, Mataram, was conducted systematically through vocalization activities, core exercises, and evaluation. The practice, presentation, and peer tutoring methods applied improved the choir members’ vocal abilities, intonation, harmonization, and appreciation of liturgical songs. Furthermore, repeated exercises helped build discipline and teamwork in liturgical services.